Research of opportunities in non-formal education for professional self-identification of future teachers - Чемоданова, Галина; Мурзалинова, Алма; Квасных, Галина (Pedagogy and Psychology, 2022)
The professional self-identification of school graduates is an urgent problem of our time. The continuous education for the formation of professional self- identification by taking into account the inclinations and interests of the young people and the demand for the profession in the labour market shall allow high school students to make the correct choice of the future professional sphere. It is proposed and substantiated to use non-formal education as a productive accompaniment to professional self- identification and “entry” into the profession.Young people that are integrated with the digital environment and, as a consequence, have the possibility to be included in non-formal education related to computerization and digitalization have been selected for the study. This has been considered by the authors in the experimental organization of interactively active communication between reputable practicing teachers and future teachers within the created Virtual Academy of continuous education. A set of theoretical and empirical research methods helped in achieving the purpose and expected results of the study and allowed diagnosing the following: a) the predisposition of school graduates to a certain professional field; b) the process of developing their axiological ideas about teaching activities; c) the effectiveness of the functional environment of professionally-oriented communication.